EFEKTIVITAS DAN KONTRIBUSI PENERIMAAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN DALAM PENINGKATAN PAD KABUPATEN MANGGARAI BARAT - Agustina Leni; Ludgardis Deliman (JURNAL ILMIAH EDUNOMIKA, 2024)
This study aims to determine the level of effectiveness of land and building rights acquisition duty revenue in increasing West Manggarai Regency local revenue and to determine the contribution of land and building rights acquisition duty in increasing West Manggarai Regency local revenue during 2019-2023. The method used in this study is descriptive research with a quantitative approach. The results obtained from this study are the effectiveness of land and building rights acquisition duties in West Manggarai Regency in 2019-2023 with a very effective average percentage of 103.805%. Meanwhile, the average contribution of land and building rights acquisition duty receipts in increasing the original income of West Manggarai Regency by 21.03% is still in the sufficient category. Keywords : Effectiveness, Contribution, PAD.